R&D Intensity, Industrial Sensitivity, and Carbon Emissions Disclosure in Indonesia - Einde Evana; Lindrianasari Lindrianasari; Rona Majidah (Indonesian Journal of Sustainability Accounting and Management, 2021)
This study examines the effect of R&D intensity and the type of industry on carbon emission disclosure (CED). The measurement of CED employs an index developed by Choi et al. (2013) based on the carbon disclosure project (CDP). The final data from this study comprise 264 company observations during the period of 2015–2018, sourced from a database of companies listed on the Indonesia Stock Exchange. The data were tested using ordinary least squares multiple regression. Results revealed that companies with lower R&D funding tend to disclose higher carbon emissions than those with higher R&D funding. Furthermore, companies whose operations are sensitive to carbon pollution are likely to disclose higher carbon emissions and vice versa. The findings indicate that there are more sensitive companies trying to fulfill their legitimacy to the public (stakeholders) compared to insensitive companies.